2018
DOI: 10.1007/s00213-017-4807-2
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin disrupts sensory and higher order cognitive processing but not pre-attentive cognitive processing—study on P300 and mismatch negativity in healthy volunteers

Abstract: Even though pre-attentive cognition (MMN) was not affected, processing at the early perceptual level (N100) and in higher-order cognition (P300) was significantly disrupted by psilocybin. Our results have implications for the role of 5-HT receptors in altered information processing in psychosis and schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 78 publications
0
19
1
Order By: Relevance
“…High dose psilocybin reduces attention to both clinical and electrophysiological parameters. However, this may be due to an increased awareness of sensory stimuli that are usually filtered out (cost of attention) rather than reduced attentional ability per se (Carter et al, 2005;Bravermanová et al, 2018).…”
Section: Cognitive Effectsmentioning
confidence: 99%
“…High dose psilocybin reduces attention to both clinical and electrophysiological parameters. However, this may be due to an increased awareness of sensory stimuli that are usually filtered out (cost of attention) rather than reduced attentional ability per se (Carter et al, 2005;Bravermanová et al, 2018).…”
Section: Cognitive Effectsmentioning
confidence: 99%
“…Disturbed cognitive processing related to psychosis as indicated by the P3 has further been investigated in the context of psychedelic drugs. Application of psilocybin to healthy subjects induced psychotic-like symptoms and a disrupted auditory P3 that decreased with increasing intensity of the psychedelic status (Bravermanová et al 2018). In previous moderate and heavy MDMA consumers, reduced P3 amplitudes in a visual discrimination task even 6 months after last drug intake indicate long lasting impairments in cognitive performance (Casco et al 2005).…”
Section: P3mentioning
confidence: 99%
“…Case reports and clinical trials have also shown a potential in the treatment of OCD (Brandrup & Vanggaard, 1977). In one patient, symptom relief persisted for a period of 5 months following a single dose (Leonard & Rapoport, 1987;Moreno, Wiegand, Taitano, & Delgado, 2006).…”
Section: Use Of Psychedelics In Contemporary Medicinementioning
confidence: 99%
“…The Czech Republic remains in the forefront of psychedelic science even todaythe Czech National Institute of Mental Health is currently conducting a clinical trial on psilocybin as a model of psychosis. To date, psilocybin has been administered to 20 healthy volunteers (Bravermanová et al, 2018). Moreover, a new multicenter research sponsored by Compass Pathways will study the use of psilocybin in a new sample of patients with treatment-resistant depression.…”
Section: Introductionmentioning
confidence: 99%